Möglichkeiten und klimarelevante Auswirkungen der stofflichen Nutzung von Kohlenstoffdioxid - Richers, Ulf (KIT Scientific Reports, 2022)
Energy transition and climate protection cause extensive changes in the German energy supply. In this context, there is an additional interest in the material utilization of carbon dioxide. The possible contributions to climate protection through material use of carbon dioxide for various products on an industrial scale are presented. Although, cultivation of algae is considered.